Implications of Gender Inequity for Achieving the Millennium Development Goals by 2015: Is Nigeria really Making Progress? (2013)
As the year of reckoning beckons, many countries are beginning to undertake a critical assessment of activities related to the Millennium Development Goals (MDGs) and the feasibility of attainment. For a country like Nigeria, it is now certain that these goals cannot be achieved in the next two years, due mainly to issues related to gender inequity. Realizing these goals even several years after 2015 will require reversal in gender relations that place males ahead of their female counterparts in virtually all spheres of life. By situating gender within the framework of the MDG-discourse, the ingredients of underdevelopment such as poverty, hunger, illiteracy, powerlessness, increasing incidence of diseases, among others, which disproportionately affect females are discussed. The paper indicates that although the MDGs have universal relevance, eliminating gender based disparities and subjugation in Nigeria should be exercised within prescribed socio-cultural norms and values given the country’s multiethnic and diverse status.